The Effectiveness of Acceptance and Commitment Therapy on Physical and Psychological Symptoms in Patients with Type 2 Diabetes - Khajepoor, Milad; Mojtabaie , Mina (Journal of Assessment and Research in Applied Counseling (JARAC), 2023)
Objective: The aim of the present study was to investigate the effectiveness of Acceptance and Commitment Therapy (ACT) on the physical and psychological symptoms of patients with type 2 diabetes. Methods and Materials: This quasi-experimental study used a pre-test, post-test design with a control group. The statistical population included all patients with type 2 diabetes in endocrinology clinics in Tehran from September to November 2021. A total of 40 patients (20 in each group) were selected through convenience sampling and randomly assigned to experimental and control groups using block randomization. The World Health Organization Quality of Life Questionnaire, the Diabetes Acceptance and Action Scale, a digital scale, and blood sugar tests were used in the pre-test and post-test. The ACT intervention was implemented for the experimental group in 8 consecutive weekly sessions. Data analysis was conducted using covariance analysis with SPSS v.27. Findings: The findings indicated a significant decrease in acceptance and action (P < 0.001, MD = -24.20, η2 = 0.50), weight (P < 0.001, MD = -9.24, η2 = 0.64), and HbA1c levels (P < 0.001, MD = -0.33, η2 = 0.34) in the intervention group compared to the control group at a significance level of less than 0.05. The post-test quality of life score in the intervention group was higher than in the control group, but this difference was not significant at the 0.05 level (P = 0.48, MD = 3.5, η2 = 0.02). Conclusion: The use of Acceptance and Commitment Therapy is effective in improving the physical and psychological symptoms of patients with type 2 diabetes, and it is recommended to be used alongside medical interventions.